2019
DOI: 10.3390/app9204375
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Nearshore Bathymetry around Ganquan Island from LiDAR Waveform and QuickBird Image

Abstract: Optical remote sensing is an effective means of water depth measurement, but the current approach of mainstream bathymetric retrieval requires a large amount of onsite measurement data. Such data are hard to obtain from places where underwater terrains are complicated and unsteady, and from sea areas affected by issues with rights and conflicts of interest. In recent years, the emergence of airborne light detection and ranging (LiDAR) provided a new technical means for field bathymetric survey. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The shipborne methods, such as echo sounding, are relatively efficient for underwater studies [274]. However, these methods are also limited over large remote ocean areas mainly due to the high cost [297,298]. Additionally, the Field surveys are time-consuming, expensive and have accessibility issues [277,296].…”
Section: Underwater Oceanmentioning
confidence: 99%
See 2 more Smart Citations
“…The shipborne methods, such as echo sounding, are relatively efficient for underwater studies [274]. However, these methods are also limited over large remote ocean areas mainly due to the high cost [297,298]. Additionally, the Field surveys are time-consuming, expensive and have accessibility issues [277,296].…”
Section: Underwater Oceanmentioning
confidence: 99%
“…The shipborne methods, such as echo sounding, are relatively efficient for underwater studies [274]. However, these methods are also limited over large remote ocean areas mainly due to the high cost [297,298]. Additionally, the applicability of this technique is negatively affected by technological restraints and environmental conditions in coastal regions [299].…”
Section: Underwater Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…Morsy et al, (2017) demonstrated that the combination of building height and spectral information achieved a clearly higher accuracy than elevation data alone in mapping urban land cover. Retrieval of bathymetry using a single spectral channel is a wellestablished lidar application but opportunities for innovations remain significant, such as the integration of mono-spectral lidar with passive multi-spectral images to map coastal water (Zhang et al, 2019). Imaging, multi-spectral lidars combine differential water absorption with range measurements to map coastal waters and the land/water boundary very accurately (Morsy et al, 2018)…”
Section: Multi-spectral Surface and Vegetation Measurementsmentioning
confidence: 99%